Phenolic fraction concentrates supplementation ameliorates learning and memory impairments in chronically stressed streptozotocin-diabetic rats by reducing brain tumor necrosis factor-α - Samir Bikri; Nada Fath; Meriam El aboubi; Asmae Hsaini; Zakia Hindi; Hajar Benmhammed; Ahmed Omar Touhami Ahami; Youssef Aboussaleh (Shahrekord University of Medical Sciences, 2022)
Introduction: The present work aims to assess if insulin combined with phenolic fraction concentrates (PFCs) prevents diabetes-related cognitive impairments by controlling neuroinflammation in streptozotocin-induced diabetic rats exposed to chronic mild stress (CMS). Methods: Directly after confirming the hyperglycemia, diabetic animals were treated with insulin combined with PFC and were exposed to 2 stressors/day for 12 weeks. Then, four cognitive tests were carried out to assess learning and memory performances. Finally, the rats were anesthetized, blood samples were collected for corticosterone and Tumor necrosis factor alpha (TNF-α) analysis, and the brain regions viz. striatum, hippocampus, and prefrontal-cortex of each hemisphere were dissected out for TNF-α analysis. Results: Both diabetes and stress could induce learning and memory impairments, which were more prominent in stressed diabetic animals, and significantly reversed by insulin treatment supplemented with PFC compared to the insulin monotherapy. Moreover, diabetic rats exposed to CMS displayed disturbances in glucose homeostasis as well as corticosterone secretion. These dysfunctions were linked to the significant increase of TNF-α in the blood as well as in the prefrontal cortex, hippocampus, and striatum. Insulin significantly ameliorated this inflammatory abnormality, while the supplemented treatment showed a significant effect, by stabilizing TNF-α to its normal levels in the hippocampus and in the blood when compared to insulin monotherapy. Conclusion: Insulin supplemented with PFC has a favorable effect over insulin alone on inflammatory aberrations linked with type 1 diabetes and stress in animals, confirming the preference of the combined treatment over insulin for the management of cognitive impairment in stressed diabetic subjects.